Online Work-Family Enrichment Self-Efficacy Program: A Pilot Randomized-Controlled Trial - Tadas Vadvilavičius; Aurelija Stelmokienė (Psychological Topics, 2025)
This paper explores the effectiveness of a newly developed online self-paced training program for work-family enrichment self-efficacy in a Lithuanian employees sample. Sixty-nine participants started the intervention, however, only twenty-two participants in the experimental group and fifteen in the control group completed the program. The experimental group participated in a three-week online self-paced intervention. The intervention consisted of short video lectures, self-reflection exercises, goal setting for a week, and a self-assessment knowledge test. The scores of work-family enrichment self-efficacy and work-family enrichment were assessed by self-reported measures at pre- and post-test. The effectiveness of the program was tested by comparing the pre- and post-test scores of work-family enrichment self-efficacy and work-family enrichment. The results revealed that work-family enrichment self-efficacy only increased in the experimental group. The changes in work-family enrichment were moderate. The new online self-paced work-family enrichment self-efficacy program showed positive outcomes. Limitations and future research directions are discussed.